The Educational Thinking of Bashir Al-Ibrahimi (1965 -1889) - Mazouzen, Samir (Milev Journal of Research and Studies, 2019)
The educational thought of Al-Bashir Al-Ibrahimi was focused on the formation, formation, and preparation of a Muslim generation in an integrated manner from all stages of individual psychological, mental, cognitive, and social development, in accordance with Islamic values ​​and principles that are closely aligned with and compatible with modern education. Accordingly, education was linked to Sheikh Al-Bashir Al-Ibrahimi on scientific grounds that carry all the parameters of changefor an individual or society. This great interest by Al-Ibrahimi to the elements educational science from the teacher and the learner and a transition to educational content indicates a conclusive indication of the Sheikh's insightful view of building the liberal thought of the learner. Hence, we strive through this article to answer the following basic problem: What are the most important educational ideas that we find in the effects of Al-Bashir Al-Ibrahimi? And to what extent are they compatible with the principles and ideas of modern education?